Answer:
Step-by-step explanation:
multiply first,
so 2√6 x √8 = 2√48 (because when radicals are multiplied we add them)
so
2√48 can be simplified to 8√3 and 2√12 can be simplified to 4√3
8√3+4√3=12√3
What?
i dont know maybe...hmmmm
Answer:
8 + k² - 6 > 8(k + 2) - 4k when k = 7
Step-by-step explanation:
8 + k² - 6 = 8 + 7² - 6 = 51
8(k + 2) - 4k = 8(7 + 2) - 4(7) = 8(9) - 28 = 44
8 + k² - 6 > 8(k + 2) - 4k when k = 7
That is about right... 2,514 X 2 = 5,028 so he is about 1,000 off. I will leave the rest to you.